2022
DOI: 10.1186/s12951-022-01286-z
|View full text |Cite|
|
Sign up to set email alerts
|

Black phosphorus-Au-thiosugar nanosheets mediated photothermal induced anti-tumor effect enhancement by promoting infiltration of NK cells in hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) is a heterogeneous cancer required combination therapy, such as photothermal therapy and chemotherapy. In recent years, cancer immunotherapies are rapidly evolving and are some of the most promising avenues to approach malignancies. Thus, the combination of the traditional therapies and immunotherapy in one platform may improve the efficacy for HCC treatment. Results In this work, we have prepared a black p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Liposome, a kind of nanoparticles (NPs) with the size of 5-500 nm, are formed by self-assembly of amphiphilic lipid molecular layers with high biosafety and long blood circulation time [ 16 ]. It is a commonly used drug carrier in cancer treatment research [ 17 , 18 ]. In addition, PEG was modified outside our liposomes to induce NP PEGylation.…”
Section: Introductionmentioning
confidence: 99%
“…Liposome, a kind of nanoparticles (NPs) with the size of 5-500 nm, are formed by self-assembly of amphiphilic lipid molecular layers with high biosafety and long blood circulation time [ 16 ]. It is a commonly used drug carrier in cancer treatment research [ 17 , 18 ]. In addition, PEG was modified outside our liposomes to induce NP PEGylation.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of pMAG/pVAE@SiO 2 -BP was obtained by the layer-by-layer assembly on the surface of SiO 2 NPs. − The morphology of products was characterized by field emission scanning electron microscopy (SEM). As seen in Figure a, the SiO 2 NPs exhibited a rough surface, irregular spherical structure, and relatively uniform mono-dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…BP functions are the most commonly strategies, including polymers functionalization [ 75 ], metal functionalization [ 76 , 77 ], and nanoparticles coating [ 78 ]. For example, Jia et al used Au-thiosugar to functionalize BP in a new study, and they found that metal ion modified BP exhibits a narrower band gap, which enhances thermal conversion efficiency [ 79 ].…”
Section: Bp-based Therapeutic Strategiesmentioning
confidence: 99%